Two new species of Xanthagaricus from Punjab, Pakistan - Haqnawaz, Muhammad; Niazi, Abdul Rehman; Khalid, Abdul Nasir (Phytotaxa, 2023)
Many basidiomata collected during a fungal survey of the Indus Riverbed revealed two new taxa in the genus Xanthagaricus. Phylogenetic analyses of the Internal Transcribed Spacers (ITS) & ribosomal Large Subunit (28S) have confirmed that these new species (namely Xanthagaricus punjabensis & Xanthagaricus kotadduensis) form a separate clade with a strong bootstrap value from the closest species of Xanthagaricus. The closest taxon to Xanthagaricus punjabensis is X. Thailandensis, while Xanthagaricus kotadduensis is closely related to X. omanicus. Xanthagaricus punjabensis is unique due to its umbonate disc, dull orange to light yellow lamellae, gray rhizomorphic mycelial mat at the base of stipe, presence of annulus, globose to subglobose basidiospore, narrowly utriform to utriform cheilocystidia, and clavate to broadly clavate caulocystidia. Our second new taxon, X. Kotadduensis, can be characterized by the absence of annulus, utriform to knobbed cheilocystidia, and oblong caulocystidia. Our results strongly support the placement of the new taxa within the genus Xanthagaricus and provide a unique insight into the phylogenetic relationships within this genus. With this addition, the number of known species of Xanthagaricus from Pakistan becomes three.